Analisis inventarisasi aset tetap (fixed asset) Pemerintah Kabupaten Bengkalis tahun 2009 - AFRIZAL, Maula ([Yogyakarta] : Universitas Gadjah Mada, 2010)
The important stage in a regional asset management system is an assets inventory in order to facilitate the collection of reliable, accurate and up to date assets data. Information on the existence and potential of these assets will support the development of the asset itself so that the regional assets could be utilized optimally and consistent with the objectives to achieve. The cuurent study was aimed to identify important factors of the fixed asset inventory of Bengkalis Regency Government owned land. The sample was 75 respondents taken by purposive sampling technique. The variables in this research are data collection, codification/labeling, grouping/classification, and recording. All variables are measured using five-point Likert scale and analyzed using Factor Analysis by the method of Confirmatory Factor Analysis. The results demonstrated that the fixed asset inventory of Bengkalis Regency Government owned land had been largely carried out in accordance with established mechanisms. Result of construct validity analysis of Confirmatory Factor Analysis (CFA) showed that the important factors of the fixed asset inventory of Bengkalis Regency Government owned land includes four basic variables, namely: data collection, codification/ labeling, grouping/classification and recording.